Risk of Stunting Events in Toddlers in the Palolo Health Center Work Area of Sigi Regency: Risiko Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Palolo Kabupaten Sigi - Hadina; Jesdika Longulo, Olkamien; Marselina Katiandagho, Laura (Poltekkes Kemenkes Palu, 2022)
Background: The Palolo Health Center is in fifth place out of 19 health centers in Sigi district that have stunting toddlers, namely 198 toddlers out of 1335 toddlers at the Palolo Health Center. The purpose of this study was to determine the risk factors associated with the incidence of stunting in children under five in the work area of ​​the Palolo Public Health Center, Sigi Regency. Methods: This study is an analytic survey using a retrospective case control. The study was conducted in March-April 2021. A sample of 116 children under five, consisting of 58 cases who experienced stunting and 58 cases that did not experience stunting, used a 1:1 comparison with gender matching. The sampling technique was probably sampling, using proportional random sampling in 15 villages. Data analysis used univariate to determine the distribution of independent frequency variables. Bivariate analysis using Chi-square test and Odds Ratio. The results of the analysis showed that the history of breastfeeding obtained p value = 0.034 (<0.05) and OR = 0.44, Birth Weight obtained p value = 0.002 (<0.05) and OR = 3.36 and Birth Body Length obtained a value p=0.041 (<0.05) and OR = 2.16. Conclusion: there is a significant relationship between the history of exclusive breastfeeding, birth weight, and birth length with the incidence of stuntin. It is hoped that health workers will increase the achievement of exclusive breastfeeding and improve the quality of ANC.